2005
DOI: 10.1348/147608305x43784
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported attachment styles and therapeutic orientation of therapists and their relationship with reported general alliance quality and problems in therapy

Abstract: The aims of this study were to explore the relationship between therapists' self-reported attachment styles and therapeutic orientation with the self-reported general therapeutic alliance and therapist-reported problems in psychological therapy.A sample of 491 psychotherapists from differing therapeutic orientations responded to a postal questionnaire. The questionnaire contained standardized measures of therapeutic alliance quality, attachment behaviours, a checklist of problems in therapy, and a brief person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 40 publications
3
85
0
3
Order By: Relevance
“…The limitations of such a design should be recognised for not taking into account the possible effect of the working alliance between therapist and patient ( [42][43][44] ). However, again, it is reassuring to note that the exercise programmes still returned better outcomes when compared to a placebo group in one study ( 25,26 ) which would tend to control for such confounding factors.…”
Section: Limitations Of the Included Studiesmentioning
confidence: 99%
“…The limitations of such a design should be recognised for not taking into account the possible effect of the working alliance between therapist and patient ( [42][43][44] ). However, again, it is reassuring to note that the exercise programmes still returned better outcomes when compared to a placebo group in one study ( 25,26 ) which would tend to control for such confounding factors.…”
Section: Limitations Of the Included Studiesmentioning
confidence: 99%
“…Dabei werden bereits zu Beginn der Ausbildung vorhandene messbare Kompetenzunterschiede zwischen den Ausbildungsteilnehmerinnen sowie der Schweregrad der Erkrankung der PatientInnen statistisch kontrolliert. (Black et al 2005;Dozier et al 1994). In einer Studie an 31 Therapeutinnen in einem stationären Setting konnten Schauenburg et al (2010) zeigen, dass die Ausprä-gung an Bindungssicherheit der Therapeutin besonders bei schwerer strukturell geschädigten Patientinnen zu einer verbesserten therapeutischen Beziehung sowie zum Therapieerfolg beiträgt.…”
Section: Methodischer Zugangunclassified
“…Ackerman and Hilsenroth's (2001) literature review on alliance suggested that therapists who were critical, uncertain, tense, distant, or distracted had poorer alliances. Some studies examined patient and therapist styles as factors influencing the alliance (Black, Hardy, Turpin, and Parry, 2005;Hietanen and Punamaki, 2006); however, on the contrary no relationship has been found in other studies (Reis and Grenyer, 2004). Additionally, another literature review on the psychotherapy alliance (Castonguay, Constantino, and Holtforth, 2006) argued that future alliance research should identify methods that The literature review underlies an importance of therapeutic change for CBT success, analysing motivation to change, mechanisms, processes and predictors of change.…”
Section: Therapeutic Change In Behavioural Disorder Treatmentmentioning
confidence: 99%